Uncovering Students’ Ability in Writing Simple Sentences Using Pictures - Asma Subur; Juhansar Juhansar; Hasse Jubba; Mustaqim Pabbajah; Nichella Ayu Clarita (Universitas Muhammadiyah Kalimantan Timur, 2023)
The development of technology affects the education sector in urban and rural areas. Teachers-students in rural areas find it difficult to apply it for some reasons. Therefore, teachers must be more creative and innovative in the learning-teaching process besides using technology, such as pictures. This research describes students' ability to write simple English sentences using pictures. The type of this research is descriptive quantitative. The respondents were tenth-grade students of SMA Negeri 29 Halmahera Selatan, which consisted of 13 males and seven females. The data were collected through an English simple sentence test consisting of 4 pictures. Each student wrote five sentences in a picture. This research showed that the mean score of students' ability to write simple English sentences using pictures is 2.95, referring to the good category. This research recommends that future research investigate the effectiveness of pictures as media used in rural and urban areas' learning-teaching process.